MEMBANGUN PENDIDIKAN MADRASAH YANG KOMPETITIF DI ERA GLOBALISASI - Basumi, Firdaus (Universitas Islam Negeri Raden Intan Lampung, 2013)
The quality control of education in Madrasas (islamic schools) can be done through three ways, i. e teacher competency enhancement, school accreditation, and, lastly, students’ achievement in the National Examination. This research was conducted to study the impacts of school accreditation among the madrasas on the teachers competency and students’ achievement in national test. The method used is so called ex post facto involving 220 teachers taken from 73 madrasas existing in 4 provinces namely: Jakarta, Central Java, South Sulawesi and South Sumatra. The study reveals that (1) There is no significant difference in performance between teachers teaching in accredited madrasas and non accredited; (2) There is a significant difference in teacher performance in every level of accreditation; (3) There is a significant difference between in the teachers performance in the accredited “B” madrasa and in the accredited “C” ; (4) There is a significant difference in the achievement of the National Examination between students from the accredited madrasas and non-acredited; (5) There is no significant difference in the results of National Examination in all levels of acreditation (A, B or C). Based on these facts, it can be concluded that school accreditation of the madrasas has real impacts on the teachers competency and students’ achievement in national test.